SOCIO-ECONOMIC IMPACT OF E-GOVERNANCE ON AGRICULTURAL GROWTH IN INDIA: A CASE STUDY OF WESTERN UTTAR PRADESH - Mohammad Junaid Alam; Tarananum (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
To provide food security, nutritional security, poverty reduction, and sustainable development in India, agriculture is a vital component of the country’s economy. It provides 17.32 percent to GDP and gross value addition of about 23.82 lakh crores INR.The Green Revolution, the Evergreen Revolution, the Blue Revolution, the White Revolution, the Yellow Revolution, the Bio-technology Revolution, and the Information and Communication Technology Revolution are some of the milestones in the Indian agricultural growth. On the other hand, information and communication technologies (ICTs) are critically analyzed in this article, in an effort to shed light on what is happening at ground level within the agricultural sector of both the country and specifically Western Uttar Pradesh.The facts are evaluated by usingsamplingmixfrom the villages, farmers, related apex bodies,concernedofficers and some of e-governance experts. The primary level opinions were gathered using questionnaires, interview schedules and spot observation of the tools and techniques of the e-governance. The research ended up with important conclusion that there is still a long way to go with regard to the execution of the egovernance tools at ground level. The traditional practices in the sector still overshadowed the e- governance in the sector. Though, there are some positive aspects also in the development of the agricultural sector, but still the main stakeholders are not connected as per the expectation of the executives of this mission in the country. As per the data it is evident that there are around 66% farm workers who have no idea about that information and the communication sources provided by the government to facilitate the agricultural & allied sectors.